Pengaruh Mata Kuliah Kewirausahaan Terhadap Minat Ber-Entrepreneur - Maria Anita Titu; Margiana Dewi Maria Madona Maran (STKIP PGRI SITUBONDO, 2022)
This study aims to determine the effect of entrepreneurship courses on the entrepreneurial interest of students at the teaching and Technology Institute of Larantuka. The hypothesis in this study is the effect of entrepreneurship courses on the entrepreneurial interest of students at the teaching and technology institute of Larantuka. The population and sample in this study found 38 people. The data collection method in this study used a questionnaire and documentation. The researcher's questionnaire was used to obtain data on entrepreneurship courses and interest in entrepreneurship. Meanwhile, the data analysis technique used to obtain the validity of the instrument is the Pearson product-moment formula and to obtain the reliability instrument, the Cronbach alpha formula. processing Based on the data obtained, the value of t-count is 2,32258 and the t-table is at a significance level of 5% with df = n – 2 = 38 – 2 = 36, which is 2.028094. Thus-the price of t-count is greater than t-table, namely 2.32258 > 2.028094. So it can be said that the hypothesis (Ha) is accepted, this shows that there is an influence of entrepreneurship courses on entrepreneurial interest in students of the Economics Education Study Program FKIP IKTL.